Lineages of "Modernism", or, how they Brought the Good News from Nashville to Oxford - Smith, Stan (Miscelánea: A Journal of English and American Studies, 1999)
The history of literary modernism reflects the twentieth century's diasporas and displacements, the construction and reconstruction of national cultures and alliances. This essay examines the retrospective construction of the idea of "modernism" in the late 1950s and 1960s, in tandem with the Americanisation of English culture and the academic institutionalisation of the modernist impulse. Robert Graves and Laura Riding, in A Survey of Modernist Poetry (1927), first introduced the term to British culture, under the influence of the Nashville journal The Fugitive, edited by Ransom, Davidson and Tate between 1922 and 1925. The concept for a while took root in the Oxford coteries around W. H. Auden in the later 1920s, but thereafter went underground until the late 1930s, when it was again invoked to characterise the Auden generation and the configuration it made with that of Eliot, Pound, Joyce, Lawrence and Yeats. Auden's departure for the United States in 1939 heralds the end of an essentially mid-Atlantic Anglophone "modernism". Not until the 1960s, however, with the simultaneous privileging of the concept of "postmodernism", does the name become generally applied, in retrospect, to a movement already in process of being superseded. Both Graves and Auden by this time have become exemplary instances of the client relationship of British and Irish modernism to a specifically American discourse.